Structure and Bioactivity Screening of a Low Molecular Weight Ulvan from the Green Alga Ulothrix flacca - Peipei Li; Songsong Wen; Kunlai Sun; Yuqin Zhao; Yin Chen (Marine Drugs, 2018)
A water-soluble low molecular–weight polysaccharide named UP2-1 was isolated and purified from the marine green algae Ulothrix flacca using ion-exchange and size-exclusion chromatography. Composition and characteristics analyses showed that UP2-1 was a sulfated glucuronorhamnan consisting of rhamnose and glucuronic acid in a ratio of 2:1 with 21% sulfate content and a molecular weight of 5.0 kDa. Structural properties were determined using desulfation and methylation analyses combined with infrared spectrum (IR), gas chromatography-mass spectrometer (GC-MS) and nuclear magnetic resonance (NMR). The results showed that UP2-1 was a type of ulvan composed of alternate 4-linked-α-L-rhamnose residues (→4)-α-L-Rha(1→) and 4-linked-β-D-glucouronoc acid residues. The sulfate groups were mainly present in the O-3 position of →4)-α-L-Rha(1→. Most (70%) of the rhamnose was sulfated. UP2-1 also had a small amount of →4)-α-L-Rha(1→ branch at the O-2 position of the →4)-α-L-Rha(1→. UP2-1 exhibited significant anticoagulant and immunomodulating activity in vitro. This study demonstrated that the green algae Ulothrix flacca, which is used as a food and traditional marine herb in China, could also be considered as a source of bioactive ulvan.